Stomatal conductivity, canopy temperature and evapotranspiration of maize (Zea mays L.) to water stress in Northeast China - Liu, Haijun; Gao, Zhuangzhuang; Zhang, Liwei; Liu, Yu (International journal of agricultural and biological engineering, 2021)
The Northeast China Plain (NECP) is one of the main maize (Zea mays L.) production regions in China but is now subject to drought because of climate change and a rain-fed cultivation system. A two-year experiment was conducted in a typical maize cultivation region in the NECP to investigate the responses of plant physiological factors and evapotranspiration (ET) to water stresses at different growth stages. Results show that the responses of plant physiological factors to water stress can be divided into three levels based on soil water content (SWC) in the main root zone: when SWC was greater than 0.22 cm3/cm3 (equivalent to 62% field capacity (FC)), stomatal conductivity (gs) and ET reached their highest values, and the canopy temperature (Tc) was close to the air temperature; when SWC was within 0.15-0.22 cm3/cm3 (43%-62% FC), the gs and ET decreased, and Tc increased as SWC decreased; and when SWC was lower than 0.15 cm3/cm3 (<43% FC), gs and ET reached their lowest values and Tc was greater than 1.2 times the air temperature. The ratio of canopy temperature to air temperature (RT), is closely related to stomatal conductivity and soil water content, and especially linearly related to crop water stress index (CWSI), and can be used as an alternative to CWSI for evaluating maize water stress because of easily data achieving and simple calculation processes. In a conclusion, RT of 1.2 can be used as an index to identify a severe water stress status, and maintaining SWC greater than 60% FC at the heading and grain-filling stages is important for supporting maize normal ET and growth in the study region.